The effect of carbon dioxide water immersing on inflammation biomarker in patients with chronic kidney disease undergoing hemodialysis - Yammar Yammar; Annisa Suwahru; Andi Rizky Arbaim Hasyar; Irfan Idris; Irawan Yusuf; Haerani Rasyid; Barangkau Barangkau (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Chronic kidney disease (CKD) patients undergoing hemodialysis (HD) often exhibit elevated levels of ICAM-1 and VCAM-1, key biomarkers of inflammation, and are prone to microcirculatory dysfunction. Recent evidence suggests that carbon dioxide (CO₂)-rich water immersion may enhance microcirculation, yet its impact on inflammatory biomarkers in CKD patients on HD remains unclear. Purpose: To evaluate the effect of CO₂-rich water immersion on ICAM-1 and VCAM-1 levels in CKD patients receiving HD. Method: This experimental study involved 22 CKD patients randomized into two groups: 14 received CO2-rich water immersion and 8 received freshwater immersion. CO2-rich water was generated using JESC CREABC-2000, with both immersions maintained at 37–38°C. Patients immersed both legs for 10 minutes, 2–3 times weekly for one month, prior to HD sessions. Blood samples were collected on day 1 and day 28. Data were analyzed using the Wilcoxon test, with statistical significance set at P < 0.05. Results: After one month, ICAM-1 and VCAM-1 levels decreased in the CO2-rich water group (42.895±58.833 to 39.690±41.911 ng/mL, P=0.650; 140.520±177.43 to 96.170±30.17 ng/mL, P=0.917). Conversely, levels increased in the freshwater group (ICAM-1: 38.642±40.975 to 63.978±80.659 ng/mL, P=1.000; VCAM-1: 100.430±34.89 to 131.920±59.80 ng/mL, P=0.461). Conclusion: CO2-rich water immersion tended to reduce ICAM-1 and VCAM-1 levels in CKD patients undergoing HD, although the changes were not statistically significant. These findings suggest potential anti-inflammatory effects warranting further investigation with larger cohorts.